Using Flies to Understand Social Networks - Jezovit, Jacob A.; Alwash, Nawar; Levine, Joel D. (Frontiers in Neural Circuits, 2021)
Many animals live in groups and interact with each other, creating an organized collective structure. The relationship between individual interactions and the collective behavior of animal groups has advanced from the application of social network analysis (SNA). SNA is a statistical tool that aids in revealing and understanding the organized patterns of shared social connections between individuals in groups. Surprisingly, the application of SNA revealed that Drosophila melanogaster, previously considered a solitary organism, displays group dynamics and that the structure of group life is inherited. Although the number of studies investigating Drosophila social networks is currently limited, they address a wide array of questions that have only begun to capture the details of group level behavior in this insect. Here, we aim to review these studies, comparing their respective scopes and the methods used, to draw parallels between them and the broader body of knowledge available. For example, we highlight how despite methodological differences, there are similarities across studies investigating the effects of social isolation on social network dynamics. Finally, this review aims to generate hypotheses and predictions that inspire future research in the emerging field of Drosophila social networks.